Pengaruh Kepuasan Kerja dan Komitmen Organisasional terhadap Turnover Intention Karyawan pada PT. Virajaya Riauputra Kecamatan Tambang - Rustian Ade Putra; Seno Andri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Turnover intention plays an important role in achieving performance success at PT. Virajaya Riauputra Tambang District in the competitive asphalt mixing plant (AMP) industry. Turnover intention at PT. Virajaya Riauputra Tambang District is influenced by several factors such as job satisfaction and organizational commitment. In order for the turnover intention rate to continue to decrease, PT. Virajaya Riauputra Tambang District must continue to improve the job satisfaction and organizational commitment of its employees in order to create a supportive work environment. The purpose of this study is to determine and analyze the effect of job satisfaction and organizational commitment on employee turnover intention at PT. Virajaya Riauputra Tambang District. This study has 71 respondents from 71 total employee populations. This study uses a sampling technique, namely census/total sampling. This study uses validation tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R2) tests. The results of this study indicate that job satisfaction and organizational commitment have a negative and significant effect on employee turnover intention at PT. Virajaya Riauputra Tambang District. This indicates that as job satisfaction improves, turnover intention decreases, and vice versa. Similarly, organizational commitment has a significant negative effect on turnover intention, this shows that higher organizational commitment leads to lower turnover intention, and vice versa.